Pengaruh Jenis Umpan Pada Alat Attractif Bait For Cockroach Trap Terhadap Jumlah Kecoak Yang Terperangkap Di Pt X - Anisa Nurul Fatah; Bambang Purnama, Lubis; Yety Hanurawaty, Neneng; Nuhayati, Ati (Poltekkes Kemenkes Bengkulu, 2024)
Cockroaches are considered vectors that can transmit diseases and pose a health threat in industrial environments. Cockroaches can transfer several patogenic microorganisms, such as Streptococcus and Salmonella. PT X is an industry that has not yet implemented vector control for disease carriers. The average population index measurement of Periplaneta americana cockroaches was 2.17, which does not meet the quality standards set by PMK No 70 of 2016. The purpose of this study was to determine the effect of different bait types on the Attractif Bait for Cockroach Trap tool on the number of cockroaches trapped at PT X. The population in this study included all cockroaches in the Paper Machine processing area, and the sample consisted of some of the cockroaches trapped using the Attractif Bait for Cockroach Trap tool. The sampling technique used was incidental sampling. This experimental study employed a posttest-only design without a control group. The sample in this study comprised 31 cockroach specimens trapped in the Paper Machine area of PT X. Data analysis using the One Way Anova test indicated that the type of bait used in the Attractif Bait for Cockroach Trap tool significantly affected the number of cockroaches trapped at PT X, with a significance value of 0.016 or <0.05. The results showed that the number of cockroaches trapped using peanut butter bait was 18 (58%), honey bait was 9 (29%), and biscuit powder bait was 4 (13%). Future researchers are advised to develop more diverse types of bait.